Macro dynamics of inflation in the Turkish economy - Sacit Sarı (Afyon Kocatepe Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
This study analyzes the macroeconomic determinants of inflation, a significant economic issue in national economies, using monthly data from January 2006 to January 2023 for the Turkish economy. Understanding inflation and its influencing factors is crucial for enhancing the effectiveness of disinflationary measures due to their adverse impacts on economic units. In this context, the relationship between inflation and selected macroeconomic variables was investigated for the Turkish economy. Based on the cointegration test results, it was established that the series are cointegrated. In the long term, money supply and interest rate variables positively impact inflation. Conversely, inflation is negatively impacted by the Industrial Production Index (IPI), which measures economic growth. This result indicates that increases in production capacity and economic growth reduce inflation. These findings suggest that the Turkish economy operates with underemployment and that monetary factors significantly impact inflation. The outcomes of the Granger causality analysis indicate a reciprocal causal relationship between inflation, money supply, and exchange rate.